1962
DOI: 10.1107/s0365110x62001176
|View full text |Cite
|
Sign up to set email alerts
|

Growth of sucrose crystals: determination of edge energy from the effect of added impurity on rate of step advance

Abstract: Quantitative experiments to investigate the effect of added impurity on the growth of sucrose crystals are described, l~ates of advance of growth steps were measured on crystals growing from pure solutions and from solutions to which raffinose was added. The temperature of the crystals was controlled at 30 °C. and the saturation ratio of the solutions was known. From the experimental results the diameter of the critical two dimensional nucleus at each saturation ratio was calculated and from this edge energy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 2 publications
3
18
0
Order By: Relevance
“…In these models, values for all physical parameters are from literature information but interface diffuseness. Future extension of this approach is sought for accounting for the effect of impurities on lateral extension of the growth steps following previous approaches [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…In these models, values for all physical parameters are from literature information but interface diffuseness. Future extension of this approach is sought for accounting for the effect of impurities on lateral extension of the growth steps following previous approaches [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which F faces grow is therefore an important factor affecting crystal morphology. Davey et al (1986) applied the dislocation theory of growth developed by Burton et al (1951)-the BCF surface diffusion model-to analyze the kinetics of crystal growth in the presence of tailor-made additives, According to Black et al (19861, the adsorption of tailor-made additives on crystal surfaces generally occurs on step sites as viewed by the Albon and Dunning (1962) model. In that model, spontaneous fluctuations produce kinks along the entire length of the step.…”
Section: Simulation Of Lattice Substitution By Impuritiesmentioning
confidence: 99%
“…The Albon and Dunning (1962) model was based on their observations of the growth of sucrose in the presence of raffinose, which may be considered a substituted sucrose molecule. Their experimental data indicated that raffinose acted as a pseudokink with a potential to reduce the step distances and increase the kink sites for adsorption.…”
Section: Simulation Of Lattice Substitution By Impuritiesmentioning
confidence: 99%
“…Impurities like invert sugar [3][4][5][6][7][8], dextran [9][10][11], raffinose [8,12,13], salts and acids [8,[13][14][15], and colour [16][17][18][19][20][21] have been investigated in the last sixty years. However, little or no information is available in the literature on the mechanisms of impurity transfer during the crystallisation process.…”
Section: Introductionmentioning
confidence: 99%